From ‘Clicks to Bricks’: A growth Strategy for SMEs - Pucar, A.; Kalfadellis, P.; O’Neill, P. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
This exploratory study investigates the ‘Clicks to Bricks’ phenomenon as it applies to SMEs looking to expand and grow their operations. This study aims to investigate the nature and viability in adopting a growth strategy for SMEs with an online presence. Using the context of Australia as the place of investigation, the study was primarily framed through the utilisation of Porter’s Value Chain as the theoretical lens of the study. This study adopted semi-structured interviews to be used in the collection of the data. Primary sampling techniques of convenience and snowball sampling were used in this study. This research found that small firms utilised it as a growth strategy to capture additional benefits that cannot be derived purely online. In setting up a physical presence the study found that there was no clearly defined path that needs to be followed nor is there any group of capabilities or resources, that must be employed to implement the strategy, as numerous different approaches including financial, the use of networks, and human resources were all shown to have worked. The process of transitioning from online to physical varied according to the capabilities and resources of the firms and the type of goods it sells.
Keywords: ‘Clicks to Bricks’, SMEs, Value Chain activities